Feasibility and Acceptability of a Web-Based Peer Navigation-Psychoeducational HIV Intervention for Women. (February 2023) - Stockman, Jamila K.; Anderson, Katherine M.; Carr, Sara G.; Wood, Brittany A.; Cloitre, Marylene; Smith, Laramie R.
This study examined feasibility, acceptability, and preliminary effects of a pilot randomized controlled trial (BRIDGES) designed to improve HIV care outcomes among syndemic-affected women living with HIV (WLHA). We enrolled and randomized adult WLHA who were out-of-care or at risk of falling out-of-care and experienced any syndemic condition(s) into BRIDGES ( n  = 11) or standard of care ( n  = 13). BRIDGES employed peer navigation one-on-one sessions and six weekly 2-h video psychoeducation group sessions. Feasibility and acceptability were assessed through participant quantitative and semistructured interviews. Intention-to-treat analyses were conducted to evaluate the preliminary effects of BRIDGES. BRIDGES was highly feasible and acceptable. Intervention participants demonstrated improved self-reported adherence to antiretroviral therapy at 3 months, and better engagement and retention in care and viral suppression at 12 months compared to control participants. BRIDGES is a promising program to provide syndemic-affected WLHA with the tools needed to mitigate social and structural barriers to HIV care.